Adopting and assimilating new non-pharmaceutical technologies into health care: a systematic review. - Robert, G; Greenhalgh, T; MacFarlane, F; Peacock, R (2010)
OBJECTIVE: To explore what is known about organizational processes that determine whether (and the extent and rate at which) new non-pharmaceutical technologies are adopted and assimilated into routine health care. METHODS: Electronic searching of four databases, hand searching of six journals and electronic citation tracking searches of three key research papers. A narrative synthesis was conducted. RESULTS: Ninety-nine empirical studies and seven narrative overviews informed the findings. The majority (62%) of the studies took a deterministic approach (mainly using cross-sectional mailed questionnaires) and typically studied the impact of organizational variables - such as organizational size - on the rate of adoption of technological innovations. The remaining studies were process-based using a single- or multi-case study approach. The organizational processes that determine whether and how technological innovations are adopted and assimilated into routine health care practice are dependent upon the specific innovation concerned, the different actors involved at various points in time, and the particular organizational context in which decisions are made. It is important to see 'adoption' and 'assimilation' as part of an ongoing process rather than discrete events, and as a process that comprises both 'formal' organizational and 'informal' decisions by individual users (the latter often shaped by discussions with their peers and colleagues). CONCLUSIONS: Further process-based studies are needed to provide a clearer evidence base for recommendations on how to facilitate the adoption and assimilation of beneficial new technologies. Three theoretical perspectives could form the basis of such studies and produce practical advice for managers and practitioners.